2023
DOI: 10.1186/s13018-023-03514-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening for genes, miRNAs and transcription factors of adipogenic differentiation and dedifferentiation of mesenchymal stem cells

Abstract: Background The purpose of present study was to reveal the molecular mechanisms responsible for both adipogenic differentiation and dedifferentiation of mesenchymal stem cells (MSCs). Methods Microarray data GSE36923 were obtained from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) between adipogenically differentiated cells vs undifferentiated bone marrow-derived MSCs, adipogenically differentiated cells vs dedifferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, in this experiment, it was observed that the miR-21 inhibitor did not significantly impact the expression of SPRY2 and ERK1/2. Ou- Yang and Dai (2023), by constructing miRNA and TF gene networks involved in MSCs adipogenic differentiation and dedifferentiation, identified 10 key miRNAs, including miR-21, and the top 10 upregulated and downregulated differentially expressed genes in pathways. This suggests that miR-21 does not singularly regulate the differentiation process through a single gene or pathway, implying the existence of multiple genes and pathways collectively governing cell fate (Yang et al, 2019;Yang, Shen, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this experiment, it was observed that the miR-21 inhibitor did not significantly impact the expression of SPRY2 and ERK1/2. Ou- Yang and Dai (2023), by constructing miRNA and TF gene networks involved in MSCs adipogenic differentiation and dedifferentiation, identified 10 key miRNAs, including miR-21, and the top 10 upregulated and downregulated differentially expressed genes in pathways. This suggests that miR-21 does not singularly regulate the differentiation process through a single gene or pathway, implying the existence of multiple genes and pathways collectively governing cell fate (Yang et al, 2019;Yang, Shen, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%